2016
DOI: 10.1039/c6fo00679e
|View full text |Cite
|
Sign up to set email alerts
|

The combined action of omega-3 polyunsaturated fatty acids and grape proanthocyanidins on a rat model of diet-induced metabolic alterations

Abstract: It has been suggested that food components such as ω-3 polyunsaturated fatty acids (ω-3 PUFAs) and (poly)phenols counteract diet-induced metabolic alterations by common or complementary mechanisms. To examine the effects of a combination of ω-3 PUFAs and (poly)phenols on such alterations, adult Wistar-Kyoto rats were fed an obesogenic high-fat high-sucrose diet supplemented, or not, for 24 weeks with: eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) 1 : 1 (16.6 g kg(-1) feed); proanthocyanidin-rich grape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 59 publications
(78 reference statements)
2
17
0
Order By: Relevance
“…Regulation of food intake and body weight may involve the microbiota‐gut‐brain axis, via which the SDF‐mediated alteration of gut microbiota and epithelial function perturbs the homeostatic humoral and neural pathways controlling food intake and body weight . Our results indicated that fermented SDF exerted significant antagonistic effect on the body weight gain of mice in a dose‐dependent manner …”
Section: Resultsmentioning
confidence: 72%
“…Regulation of food intake and body weight may involve the microbiota‐gut‐brain axis, via which the SDF‐mediated alteration of gut microbiota and epithelial function perturbs the homeostatic humoral and neural pathways controlling food intake and body weight . Our results indicated that fermented SDF exerted significant antagonistic effect on the body weight gain of mice in a dose‐dependent manner …”
Section: Resultsmentioning
confidence: 72%
“…Adiposity index: ((total abdominal fat × 100)/body weight) and hepatosomatic index: ((liver weight × 100)/body weight) were also calculated. Plasma triglycerides, total cholesterol and insulin concentrations joint to the percentage of glycated hemoglobin (HbA1c) in blood were measured in the same animals by following protocols previously described [27][28][29] and the results are currently published [30,31] . In order to facilitate the reading of the present work, a summary of those are showed in the Supplementary Tables S1 and S2, which also provide the rest of biochemical measurements done.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…According to proteomics design, comparisons among different supplements in the present research were made independently inside STD or HFHS backgrounds. The physiological effects of STD and HFHS, with or without supplements, were deeply discussed in the references [30] and [31].…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…A summary of the most relevant biochemical and biometric parameters of rats fed HFHS diets is shown in Table 1. These parameters have already been studied in the same cohort of animals and partially published [15,22,23]. Rats fed the HFHS control diet developed a prediabetic state characterized by hyperinsulinemia and excess of visceral fat [13,19].…”
Section: Effects Of Fish Oil Mixture (Fom) and Grape Seed Polyphenolsmentioning
confidence: 99%